Ideological Meaning Construction in Avatar: The Legend of Korra - ANIK, CENGİZ (MARMARA UNIV, FAC COMMUNICATION, 2018)
In recent years, with the influence of the developments in computer technology, there has been a serious increase in fantastic productions. As a product of mass culture, fantastic productions have a considerable number of viewing rates throughout the world. These productions, which are regarded as far from social reality because they are unrealistic fictions, are the media on which the ideological meaning can be built. In this work, the ideology concept will be treated as a knowledge pattern in the existing social reality, as Karl Mannheim defines within the discipline sociology of knowledge. Utopia, the other concept Mannheim uses in conjunction with ideology, is the mental codes which stand outside of the prevailing knowledge frame of society and advocate different ideas of social order. Based on the argument that even if it is fantastic, no text can be independent of the pattern of social knowledge in which it is produced; it is claimed that in every text there can be both ideological and utopian considerations. Therefore, text is one of the manifestations in which ideology and utopia become visible as the field of struggle. In this work, the ideological and utopian elements in the fantastic cartoon named Avatar: The Legend of Korra are handled and how the ideological meaning is constructed is discussed. The resulting conclusion is that in the cartoon an ideological meaning is constructed, that is to say, the liberalism represented by the US has no alternative and that US interventionism should be regarded as a sacred mission.
Keywords: Sociology of Knowledge; Ideology; Cartoons; Karl Mannheim; USA; Liberalism